Empirical essays on determinants of and attitudes towards immigration - Telli Anvernali, Henry (2011)
This thesis brings together three independent empirical essays which focus on the determinants of individual attitudes towards immigration and the determinants of migrant flows from developing countries to developed countries. The first essay looks at what happens to migrant flows from poor countries as they experience economic development. It examines the relationship between economic development in poor migrant-sending countries and migrant flows from those countries to developed countries, using the UK as a case study. The analysis in this essay relies on UK immigration data from 1973-2005 for 48 developing countries in Africa, Asia and Central and South America. The conclusion from this essay is that there is an inverse If-shape relationship between economic development and the migrant flows from developing countries to the UK, though this relationship is sensitive to aggregation of countries The second essay undertakes a comparative empirical analysis of the relative importance of the impact of economic and cultural concerns on individual attitudes towards immigration. Using data from the fourth round of the European Social Survey the study shows that there is no robust evidence to support the widely held view that economic concerns are more important than cultural concerns in shaping individual attitudes towards immigration. In the third essay a series of analyses are undertaken: first, to examine the extent to which attitudes towards immigration are determined by individual concerns about how immigration affects the welfare state; and second, to evaluate the individual characteristics that shape their subjective views regarding the effects of immigrants on the welfare state. With evidence based on the European Social Survey, the study finds that welfare state concerns are positive and robust determinants of individual attitudes towards predominantly unskilled immigration. It also finds that, older retired individuals are more likely than young or middle-aged individuals to have pessimistic views regarding the effects of immigrants on the welfare state. Hence they are also more likely to oppose immigration. By contrast, skilled individuals are more likely to have optimistic views and hence more likely to have pro-immigration attitudes than unskilled individuals.